2019
DOI: 10.1186/s40478-019-0850-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microglial TMEM119 and P2RY12 immunoreactivity in multiple sclerosis white and grey matter lesions is dependent on their inflammatory environment

Abstract: Multiple Sclerosis (MS) is the most common cause of acquired neurological disability in young adults, pathologically characterized by leukocyte infiltration of the central nervous system, demyelination of the white and grey matter, and subsequent axonal loss. Microglia are proposed to play a role in MS lesion formation, however previous literature has not been able to distinguish infiltrated macrophages from microglia. Therefore, in this study we utilize the microglia-specific, homeostatic markers TMEM119 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
90
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 41 publications
18
90
0
Order By: Relevance
“…Similarly to IBA-1, we found that both WMLs and GMLs did not show a no significant differences in expression of homeostatic microglia markers such as TMEM119 and P2RY12 (Fig. 5a,b), although a tendency to downregulation of TMEM119 in the chronic active WM demyelinated area was present corresponding to what we reported before 24 . In addition, we observed no difference in expression in leukocortical lesions of two known microglial activation markers for MS lesions, CD74 and HLA-DR ( Fig.…”
Section: Differential Gene Expression Of Microglial Related Genes In supporting
confidence: 84%
See 1 more Smart Citation
“…Similarly to IBA-1, we found that both WMLs and GMLs did not show a no significant differences in expression of homeostatic microglia markers such as TMEM119 and P2RY12 (Fig. 5a,b), although a tendency to downregulation of TMEM119 in the chronic active WM demyelinated area was present corresponding to what we reported before 24 . In addition, we observed no difference in expression in leukocortical lesions of two known microglial activation markers for MS lesions, CD74 and HLA-DR ( Fig.…”
Section: Differential Gene Expression Of Microglial Related Genes In supporting
confidence: 84%
“…By studying ITGAX at the immunohistochemical level (i.e. CD11c) we confirmed the selective regulation of CD11c in the GM area of leukocortical lesions and can thus be used as a potential new marker for a subset of microglia involved in the pathology of MS GMLs where there is no increase in HLA-DR expression at the gene and protein level 24 .…”
Section: Discussionsupporting
confidence: 57%
“…S1H, J, S2B). This expression pattern has been recently reported in early postnatal mouse brain, and shown to be associated with proliferative zones (13) and white matter (4,26,27). This cluster was found across all stages of development and all brain regions ( Fig 1D-E).…”
Section: Introductionsupporting
confidence: 83%
“…P2RY12-expressing microglia in astrocytomas were increased in low-grade but reduced in high-grade tumors [31]. Immunohistochemistry of human brain sections from multiple sclerosis cases confirmed loss of P2RY12 microglial immunoreactivity in areas associated with enhanced inflammation [22,30,32,33]. Another study in 2 AD cases showed that microglia positive for P2RY12 did not express TREM-2 [34].…”
Section: Introductionmentioning
confidence: 85%